Peran Pendidikan Agama Kristen dalam Membentuk Sikap Toleransi dan Menghargai Keberagaman di Masyarakat. - Dortin Ambalinggi; Ribka Ribka; Novrika Krisela Rantemada; Ribka Parrangan; Joyce Septikaris Ma'guling; Nopin Nopin (Jurnal Pendidikan Agama dan Teologi, 2023)
Christian Religious Education plays an important role in Forming an Attitude of Tolerance and Appreciating Diversity in Society because it is in the Religious Education Process that the process of forming an attitude based on the values of Christ continues to be echoed. This writing method uses literature studies, namely collecting various sources concerning theories that are studied based on existing topics and problems. The results of the research show that Christian Religious Teachers hold the basic principles of teaching based on the Bible. Christian Religious Teachers are the main pillars in the process of forming an attitude of Tolerance and Respect for diversity. The things that can be done by religious teachers in this case are teachers can become coaches, Friends, Facilitators to instill this attitude so that later we will see diversity in a circle that plural social